Race, solidarity and dissent in the Trayvon Martin case: a critical analysis. Issue 1 (2nd January 2016) - Yartey, Franklin Nii Amankwah
Abstract : Discourse surrounding the Trayvon Martin case spilled over to social media platforms with heated visual and textual exchanges. While supporters for Mr. Martin cried racial profiling, arguing for civil rights violation, others averred that Mr. Zimmerman's killing of Trayvon was justified because he shot him in self-defence. Many people have shared similar sentiments across the United States. Social curation site Pinterest displays thousands of images reflecting some of the national feelings on the State of Florida v. George Zimmerman. Using Lisa Nakamura's Race in Cyberspace theoretical framework, and drawing in part from semiotics, the present study critically examines some of the images of race, solidarity and dissent on Pinterest. Two themes emerged, performing white privilege and presenting a counter-discourse.